Ikonografi Zulfikar dalam Sejarah Hubungan Turki dan Nusantara - Mohamad Zahamri (Lajnah Pentashihan Mushaf Al-Qur'an, 2011)
This study explores the use of the Zulfikar motif in visual art, especially in the numerous examples of state flags and the flags of war in Turkey and the Malay World. A formal analysis is used to present a discussion of the aesthetic aspects of the artifacts. The comparative analysis examines the relationship between the use of the Zulfikar motif in Turkey and the Malay World. The study also reviews the complexities of historical relations between Turkey and the archipelago, and their connection to the use of the Zulfikar motif. Finally, this study will attempt to uncover some of the important concepts underlying the use of Zulfikar iconography in relevant historical contexts.